Feasibility of a peer-supported, WhatsApp-assisted, lifestyle modification intervention for weight reduction among adults in an urban slum of Karachi, Pakistan: a mixed-methods, single-group, pretest–post-test, quasi-experimental study - Romaina Iqbal; Iqbal Azam; Amna Rehana Siddiqui; Ali Jaffar; Sabahat Naz; Kaniz Amna Haider; Umber Khan (BMJ Open)
Objectives This pilot study assessed whether a peer-supported, WhatsApp-assisted lifestyle modification intervention for weight reduction is feasible to execute a definitive trial.Design A mixed-methods, single group, pretest and post-test, quasi-experimental study.Setting Azam Basti, an urban slum in Karachi, Pakistan.Participants Fifty participants (males and females aged 20–60) with a body mass index of >23 kg/m2, along with their nominated peers from the same family.Intervention Using motivational interviewing techniques, a trained nutritionist delivered the lifestyle modification intervention to the participants and peers for 3 days after the baseline assessment and then once monthly for 1 year. The intervention was delivered in groups using WhatsApp voice calls. The education sessions mainly focused on dietary modifications, physical activity advice and peer-support assignments to achieve a 5% wt loss from the participant’s initial body weight.Outcomes The feasibility measures included screening, recruitment, retention and monthly interview response rates. At 1 year, in-depth interviews (IDIs) with participants and peers were conducted to explore the facilitators, barriers, acceptability and experiences of the intervention. Changes in weight, calorie intake/day and calorie expenditure/day were also assessed.Results The recruitment and retention rates were 32% (n=50/156) and 78% (n=39/50), respectively, while the response rate for monthly interviews ranged between 66% (n=33) and 94% (n=47). The mean weight loss at 1 year was 2.2 kg, and the reduction in mean calorie intake was 386 kcal/day. There were no changes in the mean calorie expenditure. During the IDIs, participants and peers reported intervention via WhatsApp and peer support as convenient, flexible and supportive.Conclusions The quantitative and qualitative findings of the current pilot study support the scale-up of this work with minor modifications to the screening method as well as close monitoring and motivational interviewing to improve adherence in terms of physical activity.Trial registration number NCT05928338.